Nottinghamshire and the Great Peace: reflections on the end of the Napoleonic Wars, 1814-1815 - Gaunt, Richard A. (Maney Publishers, 2016)
This article explores Nottingham’s ambivalent attitude to the battle of Waterloo, which concluded hostilities between England and France in June 1815. It poses a contrast between Nottingham’s muted reaction to Waterloo and the town’s exuberant commemoration of the general peace between England and France the year before. The article considers different reasons for this, including Nottingham’s response to earlier set-piece battles on the continent and its reaction to domestic political events. The article explores Nottingham’s commitment to radical politics before 1815, as symbolised in its continued petitioning of parliament, and its patriotic commitment to the defeat of Napoleon Bonaparte. The article argues that it was the disappointment of the town’s hopes for economic relief, following the end of hostilities in 1814, combined with fears of a further prolonged period of conflict and delays to parliamentary reform, which helps to explain the town’s attitude during Napoleon’s ‘Hundred Days’ (March-June 1815) and after Waterloo.